FUNGSI PENGAWASAN DALAM PENERAPAN DISIPLIN KERJA PEGAWAI PADA KANTOR INSPEKTORAT DAERAH KABUPATEN MUNA - Rahmatyah, Sitti (Aksara Public, 2019)
This study aims to determine the supervisory function in the application of employee work discipline and to find out the application of employee work discipline at the Regional Inspectorate Office of Muna Regency. The collected data is then classified according to the type and source, then analyzed descriptively qualitatively by explaining or describing the data and information from each variable which is observed as it is. For primary data obtained through review of documents, interviews and observations, the data is first edited to find out the tendency to be further described based on the tendency. While secondary data is directly described after being integrated in the text or discussion. The results of the study indicate that the supervisory function in implementing work discipline at the Regional Inspectorate of Muna Regency is carried out through the direct supervision function and indirect supervisory functions.